Effect of sweetener combination and storage temperature on physicochemical properties of sucrose free white chocolate - Rodriguez Furlán, Laura (2017)
The influence of a combination of sweeteners (Stevia (St) and sucralose (Su)) and storage temperature on thermal properties, microstructure, water content, texture and Bloom of sucrose free white chocolate was investigated. A strong relationship between the microstructure and the highest percentage of Bloom was observed. The samples with 100%Su and 50%S + 50%Su presented microstructures with channels through which solids and fat could more easily spread to the surface, increasing the fat and sugar Bloom formation. However, 50%St + 50%Su and 75%St + 25%Su samples showed a minimum Bloom formation, probably due to its dense microstructure with no void spaces. The differential scanning calorimetry studies demonstrated that the samples containing 100%St and 75%St + 25%Su showed the smallest decrease of melting enthalpy with increasing temperature. Besides, non-isothermal crystallization kinetics was studied by applying Avrami model. The sample 75%St + 25%Su presented the highest values of activation energy showing the greatest stability in the temperature range studied (7 °C–30 °C).